Reactions to treatment debriefing among the participants of a placebo controlled trial - Crawford Fay; Di Blasi Zelda; Bradley Colin; Kleijnen Jos (BMC, 2005)
Abstract Background A significant proportion of trial participants respond to placebos for a variety of conditions. Despite the common conduct of these trials and the strong emphasis placed on informed consent, very little is known about informing participants about their individual treatment allocation at trial closure. This study aims to address this gap in the literature by exploring treatment beliefs and reactions to feedback about treatment allocation in the participants of a placebo-controlled randomized clinical trial (RCT). Methods Survey of trial participants using a semi-structured questionnaire including close and open-ended questions administered as telephone interviews and postal questionnaires. Trial participants were enrolled in a double-blind placebo-controlled RCT evaluating the effectiveness of corticosteroid for heel pain (ISRCTN36539116). The trial had closed and participants remained blind to treatment allocation. We assessed treatment expectations, the percentage of participants who wanted to be informed about their treatment allocation, their ability to guess and reactions to debriefing. Results Forty-six (73%) contactable participants responded to our survey. Forty-two were eligible (four participants with bilateral disease were excluded as they had received both treatments). Most (79%) participants did not have any expectations prior to receiving treatment, but many 'hoped' that something would help. Reasons for not having high expectations included the experimental nature of their care and possibility that they may get a placebo. Participants were hopeful because their pain was so severe and because they trusted the staff and services. Most (83%) wanted to be informed about their treatment allocation and study results. Over half (55%) said they could not guess which treatment they had been randomized to, and many of those who attempted a guess were incorrect. Reactions to treatment debriefing were generally positive, including in placebo responders. Conclusion Our study suggests that most trial participants want to be informed about their treatment allocation and trial results. Further research is required to develop measure of hope and expectancy and to rigorously evaluate the effects of debriefing prospectively.